BIOCHEMICAL APPEARANCE OF FATIGUE AND ITS TYPES, BIOCHEMICAL CHANGES IN THE ORGANISM DURING REST AFTER MUSCLE WORK (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The development of a temporary decrease in muscle performance during each (short or long-term, intense) work activity is called a state of fatigue. This is not a pathological condition, but is considered a normal state of the body and performs a protective function. This article provides information on the biochemical manifestation of fatigue and its types, biochemical changes in the body during the period of rest after muscle work